Study on skiing turn using passive skiing robot for improvement of game performance - Saga, N.; Saito, N. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
INTRODUCTION: Recent studies on skiing turns have been researched from various viewpoints. And the mechanism of the skiing turn using the skiing robot is clarified now. However, those results are not concretely reflected in alpine skiing. Therefore, to facilitate theoretical consideration, the passive type skiing robot was developed. The influence on the skiing turn such as the position of center-of-gravity and the shape of skiing are examined by using this robot. In this paper, it reports on their experimental results. METHOD: The robot (Figure 1) consists of the trunk, two legs, the supported bar and ski which are made from ABS resin. The trunk and each leg are combined by the hinge so that it may easily move to right and left. Further, in order to restrict the angle of the hinge, it is connected with both legs with the support bar. Using the skiing robot, we will verify experimentally how much effect is attributable to ski turning by the ski shape difference or by the centre of gravity position difference. Figure 2 shows two pairs of skis, with respective side curve radii R of 400 mm and 800 mm.